A BIOAVAILABILITY STUDY OF INDONESIAN GENERIC TABLET OF CAPTOPRIL IN HEALTHYVOLUNTEERS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Captopril is a selective inhibitor of angiotensin-converting enzyme (ACE) and is formulated by several pharmaceutical companies in Indonesia. This study was conducted to compare the bioavailability of a captopril tablet with reference products in healthy volunteers. The relative bioavailability of captopril was determined in single dose, randomized, crossover, and two-phase studies. The relative bioavailability of the test product (a generic captopril 50 mg tablet) with respect to the reference product was determined. Twelve healthy volunteers in two groups took part in these studies and took either the test or reference tablets in the first phase and received the other tablet in the second phase of each study. The bioavailability parameters include the peak concentration of captopril in serum (Cmax)